(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Agadatantra is one of the eight branches of Ayurveda that deals with toxicology. It primarily focuses on the study, prevention, diagnosis, and treatment of various toxic conditions affecting humans. Kerala has a rich and distinct tradition of Visha chikitsa renowned for its specialized therapies and effective management of venomous bites, food poisoning and environmental toxins. Many Malayalam texts that offer practical insights into toxicology, antidote formulations and indigenous treatment methods. Prayogasamuchaya is one among them which contain numerous formulations that are highly effective in managing various types of poisoning, venomous bites, and toxic conditions. Sigrusireeshadi yoga is explained in Triteeya paricheda ‘Mandali visha chikitsa’ of Prayogasamuchaya. It is indicated for external application in Mandali vishaja sopha. Swelling is the predominant symptom of viper bite, that requires emergency management. This Yoga contains 5 ingredients, including Sigru, Sireesha, Punarnava, Aswagandha and Sundi. This article aims to discuss the possible mechanism of action of Sigrusireeshadi yoga by analyzing its pharmacological properties. And the probable mode of use of this yoga in other Vishaja sopha.